Preclinical models to investigate retinal ischemia: Advances and drawbacks - Minhas, Gillipsie; Morishita, Ryuichi; Anand, Akshay (Frontiers in Neurology, 2012)
Retinal ischemia is a frequent source of irreparable visual impairment affecting over a hundred million individuals in the world. It is associated with a wide range of retinal disorders like ischemic optic neuropathies, obstructive retinopathies, carotid occlusive disorders, diabetic retinopathy and glaucoma. Compared to other tissues retina has a higher metabolic rate; any disruption in blood supply can have an effect on the supply of oxygen leading to retinal ischemia. If occlusion is not rescued the outcome is irreversible with ischemic and apoptotic cascades resulting in cell death. In addition to in-vitro models, animal models are necessary to further our understanding of the etiology, pathology, and evolution of retinal ischemia besides the evaluation, development, and improvement of therapeutic strategies. The various existing animal models of retinal ischemia are characterised by obstruction of retinal circulation that allows the study of neurovascular changes. In this review we provide an overview of major models and emerging preclinical therapeutic strategies.